2013
DOI: 10.4236/ajac.2013.49057
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Inorganic Anions Using Methacrylate-Based Monolithic Column Modified with Trimethylamine in Ion Chromatography Capillary System

Abstract: Methacrylate-based monolithic column was prepared in fused-silica capillary (80  0.32 mm i.d.) by in situ polymerizetion reaction using glycidyl methacrylate as monomer; ethylene dimethacrylate as crosslinker; 1-propanol, 1,4-butanediol, and water as porogenic solvents. The monolith matrix was modified with trimethylamine to create strong anion exchanger via ring opening reaction of epoxy groups. The morphology of the monolithic column was studied by using Scanning Electron Microscope (SEM). This column had g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In addition, when glycidyl methacrylate (GMA) is used as the monomer, the epoxy group in GMA could be easily further modified with other functional groups such as primary, secondary or tertiary amines, etc., for the separation of various compounds. We have successfully fabricated methacrylate-based monolithic columns modified with trimethylamine [73], diethylamine [74], triethylamine [75] as well as PEG [76] for the separation of inorganic anions. Compared to silica-based monoliths, these polymeric monoliths generally exhibit poorer column efficiency especially for the separation of small molecules and ions; however, the chromatographic results showed that trimethylamine-or PEG-modified monoliths could be a good alternative for the rapid determination of anions without significant swelling or shrinkage occurred in the capillary.…”
Section: Monolithic Stationary Phases For Capillary Icmentioning
confidence: 99%
“…In addition, when glycidyl methacrylate (GMA) is used as the monomer, the epoxy group in GMA could be easily further modified with other functional groups such as primary, secondary or tertiary amines, etc., for the separation of various compounds. We have successfully fabricated methacrylate-based monolithic columns modified with trimethylamine [73], diethylamine [74], triethylamine [75] as well as PEG [76] for the separation of inorganic anions. Compared to silica-based monoliths, these polymeric monoliths generally exhibit poorer column efficiency especially for the separation of small molecules and ions; however, the chromatographic results showed that trimethylamine-or PEG-modified monoliths could be a good alternative for the rapid determination of anions without significant swelling or shrinkage occurred in the capillary.…”
Section: Monolithic Stationary Phases For Capillary Icmentioning
confidence: 99%